Proposed Fire Screening Tests on Plastic Foams with a Cone Calorimeter in Hong Kong. Issue 2 (March 2013) - Chow, W.K.; Han, S.S.; Ni, X.M.
Many big building fires happened in the past involved burning furniture foam. In some places such as Hong Kong, foams treated with fire retardant additives are only required to test their ignitability under a small flame. It was proposed earlier that the behaviour of furniture foam in flashover fires should be assessed more extensively by a cone calorimeter under high radiative heat fluxes. In this paper, this screening approach is further studied using five samples, including three different pillow foams, one mattress foam and one expensive fire-safe sofa foam. Both thermal and smoke aspects were studied in a cone calorimeter under heat fluxes of 20 kWm -2, 30 kWm -2, 50 kWm -2 and 70 kWm -2 . It was observed that all the foam samples were burnt under heat fluxes above 30 kWm -2 . Only one pillow foam sample was not ignited under a low incident heat flux of 20 kWm -2, but it morphed into a mixture of solid and liquid. Under heat fluxes above 30 kWm -2, the fire-safe foam burnt vigorously; the burning showed no differences from foam without fire retardant. The fire-safe foam even released more smoke and toxic gases with higher carbon monoxide concentration. From the above cone calorimeter test, foams commonly used in the market can only withstand small match fires to delay ignition time. Foam products should be protected by additional provisions, such as an external cover, to protect them against big fires.